Recurrent heart failure hospitalizations are associated with increased cardiovascular mortality in patients with heart failure in Clinical Practice Research Datalink. (8th May 2020) - Lahoz, Raquel; Fagan, Ailís; McSharry, Martin; Proudfoot, Clare; Corda, Stefano; Studer, Rachel
Abstract: Aims: Heart failure (HF) is a leading cause of hospitalization and is associated with high morbidity and mortality post‐diagnosis. Here, we examined the impact of recurrent HF hospitalization (HFH) on cardiovascular (CV) and all‐cause mortality among HF patients. Methods and Results: Adult HF patients identified in the Clinical Practice Research Datalink with a first (index) hospitalization due to HF recorded in the Hospital Episode Statistics data set from January 2010 to December 2014 were included. Patients were followed up until death or end of study (December 2017). CV mortality as primary and as any reported cause and all‐cause mortality were evaluated. An extended Cox regression model was used for reporting adjusted relative CV mortality rates for time‐dependent recurrent HFHs. Overall, 8603 HF patients with an index hospitalization were included, providing 15 964 patient‐years of follow‐up. Patients were relatively old (median age: 80 years) and were mostly male (54.6%), with main co‐morbidities being hypertension and atrial fibrillation. Recurrent HFHs occurred one, two, three, and more than four times in 1561 (18.2%), 518 (6.02%), 206 (2.4%), and 153 (1.8%) patients, respectively. The median time to mortality was 215 (38–664) days for 50.8% of patients who died for any cause during the study period and 139 (27–531) days for 31.3% who died with CV reasons as primary cause. Compared with those of patients without recurrent HFHs, the adjusted hazard ratios (95% CI) for CV mortality as primary cause were 2.65 (2.35–2.99), 3.69 (3.06–4.43), 5.82 (4.48–7.58), and 5.95 (4.40–8.05) for those with one, two, three, and more than four recurrent HFHs. Conclusions: There is a strong association between recurrent HFH and CV mortality, with the risk increasing progressively with each recurrent HFH.